Testing and Evaluation of an IoT-Based Smart Irrigation System for Soil Moisture Monitoring - Yahya Zakaria; Imam Husen Al Munawaroh; Siti Nurul Widyaningsih; Erwin Apriliyanto (Ali Institute of Research and Publication, 2026)
Manual plant watering often does not consider real-time soil moisture conditions, which can lead to inefficient water usage. This study presents a performance evaluation of an Internet of Things (IoT)-based smart irrigation system using ESP32 for soil moisture monitoring and both automatic and manual watering control. The system was developed by integrating a soil moisture sensor with an IoT platform to support remote monitoring. Experimental testing showed an average communication delay of 1.8 seconds and automatic irrigation activation based on soil moisture thresholds: 20 seconds under very dry conditions (≤20%), 15 seconds under dry conditions (21–40%), and 5–10 seconds under moist conditions (41–59%), with irrigation stopping under wet conditions (≥60%). These results indicate that the system can provide responsive and consistent real-time irrigation control. However, the testing was conducted on a limited scale and did not include long-term field validation, so further research is needed to evaluate scalability and conduct comparative performance analysis with other systems. Academically, this study contributes to the development of a performance evaluation model for IoT-based smart irrigation systems using an adaptive threshold approach.